2021
DOI: 10.2147/rmhp.s290175
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Traumatic Brain Injury in Georgia: A Prospective Hospital-Based Study

Abstract: Purpose: Traumatic brain injury (TBI) is one of the major causes of morbidity and mortality worldwide, disproportionally affecting low-and middle-income countries (LMICs). Epidemiological characteristics of TBI at a national level are absent for most LMICs including Georgia. This study aimed to establish the registries and assess causes and outcomes in TBI patients presenting to two major trauma hospitals in the capital city-Tbilisi. Patients and Methods: The prospective observational study was conducted at Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…High fatalities among road crash patients with head injury was observed in the study of Kourouma et al (2019) as head injuries were also accompanied with lower GCS levels. 50 In contrast, another study by Burkadze et al (2021) observed longer hospital stays the more severe the injury to the brain but, they also observed that fatal brain injuries occurred the most among road crash victims. 51 It is interesting to note that a review conducted by Gupte et al (2019) found that there were sex differences regarding traumatic brain injuries, such that women were more likely to have worse prognosis from traumatic brain injuries.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…High fatalities among road crash patients with head injury was observed in the study of Kourouma et al (2019) as head injuries were also accompanied with lower GCS levels. 50 In contrast, another study by Burkadze et al (2021) observed longer hospital stays the more severe the injury to the brain but, they also observed that fatal brain injuries occurred the most among road crash victims. 51 It is interesting to note that a review conducted by Gupte et al (2019) found that there were sex differences regarding traumatic brain injuries, such that women were more likely to have worse prognosis from traumatic brain injuries.…”
Section: Discussionmentioning
confidence: 91%
“…50 In contrast, another study by Burkadze et al (2021) observed longer hospital stays the more severe the injury to the brain but, they also observed that fatal brain injuries occurred the most among road crash victims. 51 It is interesting to note that a review conducted by Gupte et al (2019) found that there were sex differences regarding traumatic brain injuries, such that women were more likely to have worse prognosis from traumatic brain injuries. 52 Women were also more likely to report worse traumatic brain injury symptoms than men.…”
Section: Discussionmentioning
confidence: 91%
“…Georgia, by virtue of its GNI per capita of US $ 4046,8, is categorized as a middle-income country that is still in the 'Centre of Development' (18). In Georgia, just like other developing countries, TBI remains one of the leading causes of mortality and disability, especially among young Georgians (19). TBI affects families, communities and societies in Georgia and have far-reaching human, social and economic costs manifested in increased emergency department visits, hospitalizations, disability and deaths.…”
Section: Introductionmentioning
confidence: 99%